Ecological history of Lachlan Nature Reserve, Centennial Park, Sydney, Australia: a palaeoecological approach to conservation. (8th April 2014) - HAMILTON, REBECCA; PENNY, DAN
SUMMARY: Reconstructing the environmental history of protected areas permits an empirically-based assessment of the conservation values ascribed to these sites. Ideally, this long-term view can contribute to evidence-based management policy that is both ecologically 'realistic' and pragmatically feasible. Lachlan Nature Reserve, a protected wetland in Centennial Park, Sydney, is claimed to be the final remnant of early and pre-European swamplands that were once extensive in the area, and the site is thus considered to have indigenous cultural and natural conservation significance. This study uses palynological techniques to reconstruct vegetation communities at the Reserve from the late Holocene to the present in order to assess whether these values adequately reflect the history, character and development of the site. The findings indicate that the modern site flora is a modified Melaleuca quinquenervia low forest assemblage formed in response to aggregated anthropogenic disturbance since colonial settlement. This assemblage replaces an Epacris -dominated heath-swampland community that was extirpated in the mid-20th century. These results emphasize the value of long-term studies in contributing to a realistic management policy that explicitly reflects the normative basis of conservation, and values the influence of past land-uses on contemporary protected ecosystems.